Differential effects of age and sex on medial temporal lobe networks revealed by longitudinal analyses across the adult lifespan. (20th December 2022) - Chauveau, Léa; Landeau, Brigitte; Dautricourt, Sophie; la Sayette, Vincent De; Chetelat, Gael; de Flores, Robin
Abstract: Background: The medial temporal lobe (MTL) is extensively connected to the rest of the brain through two specific networks which are particularly affected in Alzheimer's disease (AD): the anterior‐temporal (AT) and posterior‐medial (PM) systems. As the specific and respective effects of age and sex on the functional integrity of these networks are still largely unknown, we sought to fill this gap using longitudinal data spanning the entire adult life. Method: Longitudinal data from 215 cognitively unimpaired adults (aged 19‐85, including 113 females, followed‐up up to 47 months, 419 scans) were analysed. Seed‐based analyses were applied to resting‐state functional magnetic resonance imaging to generate connectivity maps (seeds: the perirhinal cortex for AT and the parahippocampal cortex for PM). The AT and PM networks were defined by comparing baseline maps from adults younger than 40 using a paired permutation t‐test with threshold‐free cluster enhancement (TFCE) and familywise error (FWE) correction ( p <.05) (Figure 1). These masks were then used to extract the mean functional connectivity (FC) for each participant. The interaction effects between network, age and sex were investigated using linear mixed models. Result: There was a significant interaction between age and networks ( p <.001), with a decrease of FC with age in PM and an increase in AT (Figure 2). Sex differences were also observed within these two systems ( p <.001), with males exhibiting higher FC than females in AT but lower FC in PM (Figure 3). Age‐related trajectories were not modulated by sex differences (p>.05) and were best described by a linear relationship according to model comparison testing different polynomials. Conclusion: By encompassing the entire adult lifespan and assessing longitudinal changes, our study provides strong support that the two MTL networks display differential alterations in the context of aging, as well as sex differences. Since MTL connectivity has been described as particularly affected in the early stages of AD, and age and sex are risk factors, these findings may be helpful to enhance the clinical utility of such biomarkers for the early detection of AD‐related changes.